A Cyclic Behavior of Multidirectional Box-Shaped Shearing Damper: Experimental Study - Setiawan, Angga Fajar; Awaludin, Ali; Satyarno, Iman; Md Nor, Noorsuhada; Haroki, Yusuf; Darmawan, M. Fauzi; Purnomo, Sidiq; Sumartono, Ignatius Harry (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2025)
This paper discusses an experimental study investigating the behavior of the multidirectional box-shaped shearing damper (MBSD) proposed for a bridge structures application. The MBSD consisted of a box-shaped steel plate hot coil (SPHC) material with an effective dimension of 100 x100 mm2 designed to dissipate earthquake excitation energy under combined resultant from longitudinal and transversal directions. The specimens varied with two different web slendernesses, i.e., 58.8 and 27.0. Furthermore, to investigate the different load direction effects, four different loading angles with respect to one of the web planes, i.e., 0°, 15°, 30°, and 45° to be implemented. The specimens were subjected to cyclic loading according to AISC/ANSI 341-22. In the experiment, the shear yield strength, ultimate state behavior, and energy dissipation achievement were evaluated. The result was that MBSD could achieve shear strength and sufficient energy dissipation under different angles of loading direction ranging from yielding to ultimate deformation state. The yielding and ultimate characteristics of MBSD were coincident with the ordinary shear panel damper. A stockier web resulted in a more stable stiffness after the yield point and less buckling of the web but also a slightly earlier strength degradation due to the earlier fracture damage to the welded joint. Finally, the MBSD device had visibility for application on bridge structure as a seismic device by considering appropriate strength and deformation capacity compatibility adjustment with the ultimate displacement limit of 0.11 rad drift angle. In addition, the recommendation for using a better elongation capacity steel material and less welding assembly will improve the behavior and seismic performance of the MBSD.